Brain signatures predict communicative function of speech production in interaction. (February 2021) - Boux, Isabella; Tomasello, Rosario; Grisoni, Luigi; Pulvermüller, Friedemann
Abstract: People normally know what they want to communicate before they start speaking. However, brain indicators of communication are typically observed only after speech act onset, and it is unclear when any anticipatory brain activity prior to speaking might first emerge, along with the communicative intentions it possibly reflects. Here, we investigated brain activity prior to the production of different speech act types, request and naming actions performed by uttering single words embedded into language games with a partner, similar to natural communication. Starting ca. 600 msec before speech onset, an event-related potential maximal at fronto-central electrodes, which resembled the Readiness Potential, was larger when preparing requests compared to naming actions. Analysis of the cortical sources of this anticipatory brain potential suggests a relatively stronger involvement of fronto-central motor regions for requests, which may reflect the speaker's expectation of the partner actions typically following requests, e.g., the handing over of a requested object. Our results indicate that different neuronal circuits underlying the processing of different speech act types activate already before speaking. Results are discussed in light of previous work addressing the neural basis of speech act understanding and predictive brain indexes of language comprehension.